Problemas de máximos e mínimos no Ensino Médio - Duarte, José Luís [UNESP] (2014)
The main goal of this work is to make a study about problems of maxima and minima of functions of one variable in High School. It is intended for teachers and students of mathematics of this level of learning. It intends to improve the understanding of this subject which it is often only addressed to the level of quadratic functions. It also serves as an application of the Taylor formula. In this work we want to encourage students and teachers of mathematics to the study of maxima and minima of functions of one variable. We will solve several problems involving maxima and minima of polynomial functions of the second degree, using the basic concepts of vertex, maximum point, minimum point. We will also show the resolution of problems of maxima and minima that do not lead to a quadratic function, using the derivative concept. Finally, for these last problems, we will make use of the Taylor formula in order to approximate the function obtained by its Taylor polynomial of second order. We will nd the maximum or minimum value of such polynomial by using the basic tools of quadratic function. In fact, due to Taylor theory, we will note that the optimal value obtained in the problem and the maximum or minimum value of such polynomial will be su ciently close